2015
DOI: 10.1186/s12889-015-1375-4
|View full text |Cite
|
Sign up to set email alerts
|

A worksite intervention to reduce the cardiovascular risk: proposal of a study design easy to integrate within Italian organization of occupational health surveillance

Abstract: BackgroundDespite the substantial amount of knowledge on effectiveness of worksite health promotion (WHP) in reducing cardiovascular disease (CVD) risk, WHP programs are not systematically applied in Italy. The aim was to design an intervention easy to integrate within the Italian organization of workplace health surveillance.MethodsWe used the “pretest-posttest design”. Workers were employed in multiple occupations and resident in Veneto region, Italy. Occupational physicians (OPs) performed all examinations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
3
Order By: Relevance
“…(6) Despite the increased interest in this kind of studies, however, not many reports are found in the literature because, when the studies are developed in the work environment, they can be impaired by the existence of a research bias, which interferes in the internal validity of its results. (18) It is highlighted that, like in this study, the possibility of information exchange between the groups is a very frequent bias when the study is developed in industrial companies/ services. (19) Independently of whether information was exchange between the groups, another aspect that should be considered in the comparison of the results with other studies is the difference between the populations, as this study only involved men, while most other studies, mainly international research, which have identified a significant increase in knowledge on risk factors for cardiovascular diseases, were developed with female populations (2,24) or populations with a large share of female participants.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…(6) Despite the increased interest in this kind of studies, however, not many reports are found in the literature because, when the studies are developed in the work environment, they can be impaired by the existence of a research bias, which interferes in the internal validity of its results. (18) It is highlighted that, like in this study, the possibility of information exchange between the groups is a very frequent bias when the study is developed in industrial companies/ services. (19) Independently of whether information was exchange between the groups, another aspect that should be considered in the comparison of the results with other studies is the difference between the populations, as this study only involved men, while most other studies, mainly international research, which have identified a significant increase in knowledge on risk factors for cardiovascular diseases, were developed with female populations (2,24) or populations with a large share of female participants.…”
Section: Discussionmentioning
confidence: 80%
“…This can easily happen with educational interventions in the work environment, as the participants naturally share/disseminate information with other colleagues, which can threaten the internal validity of results. 18) In addition, this type of situation is unwanted to assess an intervention, as it reduces the differences observed between the intervention and control groups. 19) Nevertheless, from a Public Health perspective, the fact that the control group benefited from the intervention due to the information exchange is something positive, as these participants also increased their knowledge about the risk factors for CVD, enhancing the prevention of these outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los programas de promoción de la salud en el sitio de trabajo pueden modificar factores de riesgo como inactividad física, tabaquismo, hipertensión, dislipidemia, mala alimentación, hiperglucemia y estrés psicológico elevado; y aunque los empleadores consideren que la tarea de mejorar la salud de sus empleados le corresponde a las instituciones de salud, debido a las jornadas de trabajo las personas no pueden asistir a los servicios de atención, el escenario laboral entonces se convertiría en una opción para fomentar estilos de vida saludable (18,19). El diseño de corte transversal en una limitación de esta investigación porque no permite establecer inferencias causales entre las variables estudiadas, aunque si la postulación de hipotesis causales que permitan plantear futuras investigaciones.…”
Section: Discussionunclassified